Communication of the Setu Tujuh Muara Depok Tourism Awareness Group in Nature Tourism Management - Agustini Agustini; Robby Firliandoko; Apriansyah Apriansyah (Journal of Innovative and Creativity, 2026)
This study examines the role of the Tourism Awareness Group (Pokdarwis) in strengthening local ecotourism potential in Setu Tujuh Muara, Bojongsari, Depok. Using a descriptive qualitative approach, data were obtained through in-depth interviews, participatory observation, and documentation involving Pokdarwis members, the surrounding community, visitors, and relevant stakeholders. The results indicate that Pokdarwis has a strategic role in environmental management, tourism facility development, community economic empowerment, digital promotion, and mobilizing citizen participation. Group communication within Pokdarwis runs effectively through social, educational, persuasive, problem-solving, and coordination functions that support organizational sustainability. Pokdarwis is able to increase community participation, tourism-based income, and environmental awareness. However, there are obstacles such as limited funds, suboptimal infrastructure, and institutional legality that has not been fully completed. This study concludes that group communication and community involvement are the keys to developing sustainable ecotourism in Setu Tujuh Muara.